Porcine granulosa cell transcriptomic analyses reveal the differential regulation of lncRNAs and mRNAs in response to all-trans retinoic acid - Jinzhu Meng; Xiuwen Chen; Huabiao Wang; Yixuan Mi; Runsheng Zhou; Hongliang Zhang (Animal Bioscience)
Objective The active metabolite of vitamin A, all-trans retinoic acid (ATRA), is involved in the proliferation and differentiation of granulosa cells, and promotes the follicular development, oocyte maturation, and ovulation in mammals. This study aims to investigate the ATRA induced potential long noncoding RNAs (lncRNAs) that regulate the expression of genes associated with granulosa cell proliferation and follicular development. Methods The lncRNA and mRNA profiles of porcine granulosa cells from ATRA treatment and control group in vitro were constructed through RNA sequencing. Meanwhile, the sequencing data were verified using quantitative polymerase chain reaction (qPCR). Results A total of 86 differentially expressed lncRNAs and 128 differentially expressed genes (DEGs) were detected in granulosa cells after ATRA treatment. The quantitative real-time PCR (qRT-PCR) results were consistent with the RNA-seq data. Functional annotation analysis revealed that the DEGs were remarkably enriched in ovary function and reproduction which contained FoxO, Hippo, Oocyte meiosis, mammalian target of rapamycin signaling pathway, as well as several pathways associated with hormone regulation like oxytocin signaling pathway and steroid hormone biosynthesis. Moreover, an interaction network of lncRNAs and their cis-target DEGs was constructed, and 7 differentially expressed lncRNAs and 6 cis-target DEGs were enriched in ovarian steroidogenesis and reproduction. Conclusion These findings expand the lncRNA catalogue and provide a basis for further studies on the mechanism of ATRA-mediated lncRNA regulation of follicular development in pigs.